Urban oases: the social-ecological importance of small urban green spaces - Monika Egerer; Peter Annighöfer; Sophie Arzberger; Stefanie Burger; Yannik Hecher; Vera Knill; Birgit Probst; Michael Suda (Ecosystems and People, 2024)
Global challenges around biodiversity loss, climate change, and public health are heightening the importance of urban green spaces for supporting ecosystem services and human wellbeing. Trees, parks and forests integrated across cityscapes are proposed strategies to combat climate change and promote human health for current and future cities. This is true for small urban green spaces, perhaps just < 1 ha in size. Depending on their structure and size, these spaces can provide structural vegetation complexity, promote species diversity, regulate temperatures and offer human thermal comfort. These spaces also provide recreation opportunity, nature experience, sense of belonging, and restoration to people. As cities densify, it is crucial to understand where these dimensions intersect in theory and practice to design and manage small green spaces in particular, as these systems may be easier than large green spaces to implement in urban planning. In this paper, we narratively review known biophysical and ecological properties of green spaces that support biodiversity, promote temperature regulation and climate resilience, and may ultimately benefit residents’ health through different use activities and multisensory experiences that promote restoration and wellbeing. Furthermore, we review how stakeholder engagement and participatory processes can guide equitable green space provision and design, and we use case studies and our own research as examples. In doing so, this paper aims to further the understanding of the social-ecological importance of small urban green spaces and calls for inter- and transdisciplinary research that generates insight to design, manage and protect these places in a changing climate.